Analysis of the Role Whistleblowing System for Fraud Pervention: Theory of Planned Behavior - Amalia Ramadhani, Mesra; Trisnaningsih, Sri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
The existence of economic development makes the business world also develop and of course it will be more complex, the practice of crime in the form of fraud is also developing. Corruption cases are ranked first in the most detrimental fraud cases in Indonesia. Most fraud is carried out by internal companies because most of them already know where the loopholes are. This form of prevention can be carried out through a whistleblowing system, where as one of the effective control mechanisms in detecting fraud or fraud within the organization. The term for whistleblowing system reporters is whistleblower. By carrying out a whistleblowing system action, many threats and risks will be faced by the reporter. So this study uses the Theory of Planned Behavior in describing an intention to commit fraud (cheating). This research is qualitative by using a literature review approach. In this study using secondary data. This study explains that the application of the theory of planned behavior is a reference for companies in improving the whistleblowing system to anticipate fraud prevention, in which there are three factors, namely: Attitude, individual perception to do or not to do a behavior and readiness or ability to control that behavior. lead to whistleblowing behavior.